A review of insulin and insulin regimens in type 2 diabetes - S. Joshi; P. Joshi (South African Family Practice)
We have reviewed the various insulins available in the South African market, together with the modes of action of each of the formulations. The insulin groups discussed include the Basal insulins, the bolus or prandial insulins, and the premixed insulins. Furthermore, an approach to the designing of an insulin regimen is discussed, and comments made on how to further intensify therapy depending on the response experienced. Oral hypoglycaemic agent failure is defined by an HbA 1C measurement that exceeds 7%, which is a definitive call for further therapy with insulin in type 2 diabetes.